An Improved Mathematical Model of Thermal Physiological Response of Naked Infants (Journal of Fiber Bioengineering and Informatics, 2009)
In this paper, an improved 9-node mathematical model of thermal physiological response of infants is developed by integrating Gagge's two-node model and Stolwijk's multi-node model. Considering the individual difference of infant's body weight and size, the relationship between basic geometric parameters of infants and their thermal physiological parameters has been established in this model, so that the new naked infant model can be used for different size of infants, term infants and premature infants. To investigate the core and skin temperature distribution on infants, a set of numerical simulations have been carried out for naked, premature and term infants. By comparing the predictions of the model with the published data, this model was validated in the aspects of neutral thermal environment and skin temperature distribution. It was found that this model is satisfactory.
Keywords: Physiological response; infant; thermal comfort; mathematical model; numerical simulation; temperature distribution